2020
DOI: 10.4314/ahs.v20i4.59
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the prevalence and predictors of anemia among children in Ethiopia

Abstract: Background: Anemia is a wide-spread public health problem characterized by a decrease in hemoglobin concentration and/ or red blood cell volume below an established cut-off value. In developing countries including Ethiopia, about half of children are estimated to be anemic. Therefore, the purpose of this study was to determine the pooled prevalence of anemia and its predictor factors among children in Ethiopia. Method: The studies were identified through explicit and exhaustive search of reputable databa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 94 publications
2
13
2
Order By: Relevance
“…In order to turn on the health loss due to anemia in children, UNICEF and WHO jointly recommended adequate breastfeeding practices [ 67 ]. But the finding of this study is inconsistent with a systematic review and meta-analysis study conducted in Ethiopia [ 64 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In order to turn on the health loss due to anemia in children, UNICEF and WHO jointly recommended adequate breastfeeding practices [ 67 ]. But the finding of this study is inconsistent with a systematic review and meta-analysis study conducted in Ethiopia [ 64 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Mothers with informal education were 53% more likely to have child with anemia. This finding is in line with a systematic review and meta-analysis study conducted in Ethiopia [ 64 ]. This might be because mothers with no formal education may not understand the introduction of scientifically sound feeding practices and are less likely to follow the recommended child feeding practices [ 65 ].…”
Section: Discussionsupporting
confidence: 92%
“…According to studies reported on the prevalence and associated factors of anemia, the prevalence of anemia has significant variation across regions in Ethiopia [ 7 , 28 34 ]. Therefore, this study aimed to investigate spatial regression analysis of anemia and its associated factors among children aged 6–59 months.…”
Section: Introductionmentioning
confidence: 99%
“…This study contrasts with Gebrie's research which shows that mothers without formal education have a 1.3 times higher risk of anemia than those with formal education. 26 Educated mothers will give more attention to infants' health care and provide a variety of nutritious and iron-rich foods. 27,28 Simbauranga et al stated that there is a relationship between maternal employment and the incidence of IDA.…”
Section: Discussionmentioning
confidence: 99%